If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(3x + 10) + -2 = 5 Reorder the terms: qrst(10 + 3x) + -2 = 5 (10 * qrst + 3x * qrst) + -2 = 5 (10qrst + 3qrstx) + -2 = 5 Reorder the terms: -2 + 10qrst + 3qrstx = 5 Solving -2 + 10qrst + 3qrstx = 5 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 10qrst + 2 + 3qrstx = 5 + 2 Reorder the terms: -2 + 2 + 10qrst + 3qrstx = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 10qrst + 3qrstx = 5 + 2 10qrst + 3qrstx = 5 + 2 Combine like terms: 5 + 2 = 7 10qrst + 3qrstx = 7 Reorder the terms: -7 + 10qrst + 3qrstx = 7 + -7 Combine like terms: 7 + -7 = 0 -7 + 10qrst + 3qrstx = 0 The solution to this equation could not be determined.
| -0.10(34)+0.25x=0.05(x-12) | | =6(-5)+30 | | 10*n=110 | | 15=02z | | 7y-15= | | 22+2q=37+6+q | | 1.2=0.2k | | (x*.20)+x=5780 | | =6(-1)+30 | | -log(x)=8.42 | | 0.75x+0.05(16-x)=0.10(-62) | | d^2+d-400=0 | | -2x+3=19+6x | | 5m=0.95 | | u^5-13u^2+36=0 | | 8(8)-11= | | 4-x+7+5x= | | -2x-5-2(x-3)=9x-(7x-8)-8x+5 | | -6(10+8)+9(5r+8)= | | -39-35= | | 5.5t=22 | | 4x+9=47 | | 3y-4/5y=22 | | -8-5f=12-9f | | 65+(4x-1)=180 | | 19-2n=-9 | | 2(x-10)+4x=-6x+2 | | n/8=28/32 | | 3y-4y=22 | | 8f=36 | | -18w-3+3w-12= | | -2x-5-2(x-3)=2x-(7x-8)-8x+5 |